Trade as a tool for the economic empowerment of women (UN NewUS, 2016)
Explores the gender and trade nexus focusing on three sectors: agriculture, manufacturing and services. Includes a comprehensive examination of the treatment of gender equality and women's economic empowerment within the the new global development frameworks, the 2030 Agenda for Sustainable Development and Addis Ababa Action Agenda on financing for development.
Note by the UNCTAD Secretariat.